Heat transfer suppressing sheet and battery pack

By using heat transfer inhibitors containing dry silica particles and fine pores in the battery pack, the problem of insufficient heat propagation inhibition effect of the battery pack is solved, and better thermal insulation performance and safety are achieved. It is suitable for electric vehicles. etc.

CN222168526UActive Publication Date: 2024-12-13IBIDEN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420565515.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2024-03-21
Publication Date
2024-12-13
Estimated Expiration
2034-03-21

AI Technical Summary

Technical Problem

In the case of thermal runaway, the heat propagation suppression effect is insufficient, especially in applications such as electric vehicles, which require better thermal insulation performance to ensure the safety of passengers.

Method used

A heat transfer inhibiting sheet containing dry silica particles and fine pores is used to improve thermal insulation performance by controlling the particle size and pore volume ratio, and appropriately configured in the battery pack to suppress heat propagation.

Benefits of technology

It significantly improves the thermal insulation performance of the battery pack, prevents thermal runaway and flame spread outward, ensures passenger safety, and reduces the cost of the battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222168526U_ABST
    Figure CN222168526U_ABST
Patent Text Reader

Abstract

The utility model provides a heat transfer suppression sheet and a battery pack, the heat transfer suppression sheet has excellent heat insulation performance, and the battery pack is provided with the heat transfer suppression sheet. The heat transfer suppressing sheet (10) contains dry silica particles (1) and has pores (2) therein. The dry silica particles (1) have an average primary particle diameter of 25 nm or less, and the total volume of pores having a mode diameter of 68 nm or less is 10% or more relative to the total volume of pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a heat transfer suppression sheet and a battery pack having the heat transfer suppression sheet. Background Art

[0002] In recent years, from the perspective of environmental protection, electric vehicles and hybrid vehicles driven by electric motors have been developed. These electric vehicles and hybrid vehicles are equipped with a battery pack composed of a plurality of battery cells connected in series or in parallel as a power source for the driving electric motor.

[0003] In addition, the battery cells mainly use lithium-ion secondary batteries that can achieve higher capacity and higher output than lead-acid batteries, nickel-metal hydride batteries, etc. Furthermore, in the case of thermal runaway where a battery cell rapidly heats up and continues to heat up due to internal short circuits, overcharging, etc. of the battery, the heat from the battery cell that has thermal runaway will spread to other adjacent battery cells, which may cause thermal runaway of other battery cells.

[0004] As a method of suppressing the propagation of heat from a battery cell that has undergone thermal runaway as described above, a method of interposing a heat insulating sheet between battery cells is generally performed.

[0005] For example, Patent Document 1 discloses a thermal insulation sheet for a battery pack, which includes first particles composed of silica nanoparticles and second particles formed of metal oxides, and the content of the first particles is limited. In addition, Patent Document 1 states that the thermal insulation sheet may include a binding material composed of at least one selected from fibers, adhesives, and heat-resistant resins.

[0006] In addition, Patent Document 1 described above states that dry silica or wet silica can be used as the first particles, and that the thermal insulation sheet can be produced by a dry molding method or a wet papermaking method.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-34278 Utility Model Content

[0010] Technical problems to be solved by the utility model

[0011] In addition, the battery pack used in recent electric vehicles (EV) and the like is sometimes arranged under the floor of the passengers. In this case, in order to ensure the safety of the passengers, a heat transfer suppression sheet having a better heat insulation performance is required.

[0012] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a heat transfer suppressing sheet having excellent heat insulation performance, a method for producing the same, and a battery pack having the heat transfer suppressing sheet.

[0013] Means for solving technical problems

[0014] The above object of the present invention is achieved by the following structure [1] of the heat transfer suppression sheet.

[0015] [1]. A heat transfer suppressing sheet comprising dry silica particles and having pores therein, characterized in that:

[0016] The average primary particle size of the dry silica particles is less than 25 nm.

[0017] The total volume of pores having a mode diameter of 68 nm or less is 10% or more of the total volume of the pores.

[0018] In addition, preferred embodiments of the present invention related to the heat transfer suppression sheet relate to the following [2] to [7].

[0019] [2] In the heat transfer suppression sheet of [1], it is characterized in that

[0020] The dry silica particles have an average primary particle size of 7 nm or more.

[0021] [3] In the heat transfer suppression sheet of [1] or [2], characterized in that

[0022] The total volume of the pores having a mode diameter of 68 nm or less is 15% or more of the total volume of the pores.

[0023] [4] In any one of [1] to [3], the heat transfer suppressing sheet is characterized in that:

[0024] The total volume of the pores is 2.0 cc / g or more.

[0025] [5] In any one of [1] to [4], the heat transfer suppressing sheet is characterized in that:

[0026] In the heat transfer suppressing sheet, the small-diameter dry silica particles enter into gaps between the large-diameter inorganic particles.

[0027] [6] In the heat transfer suppression sheet of [5], it is characterized in that

[0028] The inorganic particles and the dry silica particles are held by a binder portion.

[0029] [7] In any one of [1] to [6], the heat transfer suppressing sheet is characterized in that:

[0030] The surface of the heat transfer suppressing sheet is covered with a film.

[0031] The above-mentioned object of the utility model is achieved by the following structure [8] of the battery pack.

[0032] [8] A battery pack, characterized in that the battery pack has a plurality of battery cells and the heat transfer suppression sheet according to any one of [1] to [7], wherein the plurality of battery cells are connected in series or in parallel.

[0033] In addition, a preferred embodiment of the present invention related to the battery pack relates to the following [9].

[0034] [9]. In the battery pack of [8], characterized in that

[0035] The heat transfer suppression sheet is disposed between battery cells and / or between a battery cell and a battery case.

[0036] Utility Model Effect

[0037] The heat transfer suppressing sheet of the present invention contains dry silica particles with a controlled average primary particle size, has pores inside, and limits the volume ratio of pores with a diameter below a predetermined value, so that excellent heat insulation performance can be obtained.

[0038] According to the battery pack of the present invention, since the heat transfer suppression sheet having excellent heat insulation performance as described above is provided, thermal runaway of the battery cells in the battery pack and spread of flames to the outside of the battery case can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram showing an enlarged view of a part of the heat transfer suppression sheet according to the embodiment of the present invention.

[0040] Figure 2 This is a graph showing the relationship between the specific surface area of ​​dry silica particles and the thermal insulation performance when the horizontal axis represents the specific surface area of ​​the dry silica particles and the vertical axis represents the peak temperature of the non-heating surface of the heat transfer suppressing sheet.

[0041] Figure 3 This is a graph showing the pore size distribution of dry silica particles per average primary particle size, with the vertical axis representing the pore volume and the horizontal axis representing the pore size.

[0042] Figure 4 This is a graph showing the relationship between the average primary particle size and the pore size, when the vertical axis represents the pore size (modal diameter) and the horizontal axis represents the average primary particle size of the dry silica particles.

[0043] Figure 5This is a graph showing the relationship between the average primary particle size and the volume ratio, when the vertical axis represents the volume ratio of pores having a mode diameter of 68 nm or less and the horizontal axis represents the average primary particle size of dry silica particles.

[0044] Figure 6 It is a schematic diagram showing a battery pack according to an embodiment of the present invention.

[0045] Description of Reference Numerals

[0046] 1: Dry silica particles;

[0047] 2: fine pores;

[0048] 3: Adhesive part;

[0049] 4: Heat conduction;

[0050] 10: Heat transfer suppression sheet;

[0051] 20a, 20b, 20c: battery cells;

[0052] 30: battery housing;

[0053] 100: Battery pack. DETAILED DESCRIPTION

[0054] The inventor of the utility model conducted in-depth research on a heat transfer suppression sheet that can further improve the thermal insulation performance. As a result, it was found that the following is effective: the heat transfer suppression sheet contains dry silica, the average primary particle size of the dry silica is appropriately specified, and the volume ratio of pores of a specified size formed in the heat transfer suppression sheet is specified.

[0055] Hereinafter, the heat transfer suppression sheet and the manufacturing method thereof and the battery pack according to the embodiment of the present invention will be described in detail. In addition, the present invention is not limited to the embodiment described below, and can be implemented with arbitrary changes within the scope not departing from the gist of the present invention.

[0056] [Heat transfer suppression sheet]

[0057] Figure 1 Schematic diagram showing a part of the heat transfer suppression sheet according to an embodiment of the present invention in an enlarged manner. Figure 1 As shown, the heat transfer suppressing sheet 10 includes dry silica particles 1 and has a plurality of fine pores 2 inside. And, the dry silica particles 1 are held by, for example, a binder portion 3. First, the dry silica particles 1 and the fine pores 2 will be described in detail.

[0058] <Dry Silica Granules>

[0059] The dry silica particles 1 contained in the heat transfer suppressing sheet 10 of the present embodiment are made of silica with high heat insulation properties, for example, nanoparticles having a spherical or nearly spherical shape and an average primary particle size of 25 nm or less. Such nanoparticles have low density, so they suppress conductive heat transfer, and the pores are finely dispersed, so excellent heat insulation properties that suppress convective heat transfer can be obtained.

[0060] In addition, since the dry silica particles 1 have excellent compression characteristics, excellent effects can be obtained in a battery pack in which the heat transfer suppression sheet 10 is interposed between multiple battery packs. Specifically, even when the heat transfer suppression sheet 10 is compressed due to expansion associated with thermal runaway of the battery cell and the internal density increases, the increase in conductive heat transfer of the heat transfer suppression sheet 10 is suppressed. The reason for this is believed to be that nanoparticles are easily filled in a buffering manner due to the repulsive force generated by static electricity.

[0061] (Average primary particle size of dry silica particles: 25 nm or less)

[0062] Figure 2 This is a graph showing the relationship between the specific surface area of ​​dry silica particles 1 and the thermal insulation performance, with the horizontal axis being the specific surface area of ​​dry silica particles 1 and the vertical axis being the non-heating surface peak temperature of the heat transfer suppression sheet. The non-heating surface peak temperature on the vertical axis is a value obtained by measuring the peak temperature of the other main surface of a pair of main surfaces of a heat transfer suppression sheet made using dry silica particles 1 having various average primary particle sizes, while being pressurized at a specified pressure, heating one of the main surfaces at a temperature of, for example, 800°C for a specified time. In addition, all of these heat transfer suppression sheets are manufactured under the same conditions, with only the average primary particle size of the dry silica particles 1 being changed. In addition, Figure 2 The aggregated particle size and water content of the dry silica particles having each average primary particle size are also shown.

[0063] like Figure 2 As shown in the figure, when the average primary particle size of the dry silica particles 1 is 30 nm, the non-heating surface peak temperature exceeds 190°C, and excellent heat insulation performance cannot be obtained. This is considered to be because when the average primary particle size of the dry silica particles 1 is large, the contact area between the particles increases, and the contact points between the particles decrease, so the heat conduction between the solids increases. On the other hand, when the average primary particle size of the dry silica particles 1 is 25 nm or less, as shown in the figure, the non-heating surface peak temperature exceeds 190°C, and excellent heat insulation performance cannot be obtained. This is considered to be because when the average primary particle size of the dry silica particles 1 is large, the contact area between the particles increases, and the contact points between the particles decrease, so the heat conduction between the solids increases. Figure 1As shown, the contact area between the dry silica particles 1 decreases, the contact points between the particles increase (interface resistance increases), and thus the heat conduction 4 between the solids decreases. Therefore, the average primary particle size of the dry silica particles 1 is set to 25 nm or less, preferably 20 nm or less, and more preferably 15 nm or less.

[0064] On the other hand, in the present embodiment, the lower limit of the average primary particle size of the dry silica particles 1 is not particularly limited. As described above, when the average primary particle size of the dry silica particles 1 is small, the heat conduction 4 is reduced and the heat insulation performance is improved. However, depending on the storage conditions of the heat transfer suppression sheet 10, as the specific surface area of ​​the dry silica particles 1 increases, the amount of water adsorbed on the heat transfer suppression sheet 10 may increase. Furthermore, if the amount of water contained in the heat transfer suppression sheet 10 increases, the particles agglomerate with each other and the contact area increases, and as Figure 2 As shown in FIG. 1 , as the aggregated particle size increases, the diameter of the pores 2 formed in the heat transfer suppressing sheet 10 also increases. As a result, the heat transfer caused by heat conduction and convection increases, so the heat insulation performance is saturated. Therefore, in order to suppress the adsorption of water on the heat transfer suppressing sheet 10 and further improve the heat insulation performance, the average primary particle size of the dry silica particles 1 is preferably 7 nm or more.

[0065] Furthermore, the bulk density of the dry silica particles 1 having an average primary particle size of 25 nm or less is about 0.005 g / cm 3 Therefore, for example, even if the battery cells arranged on both sides of the heat transfer suppressing sheet 10 thermally expand and a large compressive stress is applied to the heat transfer suppressing sheet 10, the size of the contact points between the dry silica particles 1 does not increase significantly, and the thermal insulation can be maintained.

[0066] (Content of dry silica particles: 50% by mass or more and 80% by mass or less)

[0067] If the content of dry silica particles in the heat transfer suppression sheet relative to the total mass of the heat transfer suppression sheet is appropriately specified, the volume ratio of pores having a specified mode diameter described later can be controlled. That is, in order to obtain the volume ratio of pores described later, the content of dry silica particles is preferably 50% by mass or more and 80% by mass or less. In addition, the content of dry silica particles in the heat transfer suppression sheet can be measured by chemical analysis methods such as fluorescent X-ray analysis (XRF: X-Ray Fluorescence) and ICP emission spectrometry (ICP-AES: Inductively Coupled Plasma Atomic Emission Spectroscopy).

[0068] <Pore>

[0069] (Total volume of pores with a mode diameter of 68 nm or less: 10% or more)

[0070] The heat transfer suppressing sheet 10 of the present embodiment has a plurality of pores 2 inside. The influence of the size of the pores 2 on the heat insulation performance will be described in detail below. Figure 3 This is a graph showing the pore size distribution of the dry silica particles 1 for each average primary particle size, with the vertical axis representing the pore volume and the horizontal axis representing the pore size. Figure 4 This is a graph showing the relationship between the average primary particle size and the pore size, when the vertical axis represents the pore size (modal diameter) and the horizontal axis represents the average primary particle size of the dry silica particles. Figure 5 This is a graph showing the relationship between the average primary particle size and the volumetric ratio when the vertical axis is the volumetric ratio of pores with a mode diameter of 68 nm or less and the horizontal axis is the average primary particle size of dry silica particles. Figure 3 In the graph, the peaks appearing in the range of pore diameters of 100 nm or less represent pores originating from primary particles of the dry silica particles 1. In addition, the gentle peaks appearing in the range of pore diameters exceeding 100 nm represent pores originating from secondary particles and tertiary particles of the dry silica particles 1.

[0071] The size of the pores 2 affects the thermal insulation performance. That is, if the size of the pores 2 exceeds 68nm, which is the mean free path of air, collisions between molecules and collisions between molecules and the wall will occur, and heat will be transferred by both convection and heat conduction. On the other hand, if the size of the pores 2 is less than the mean free path of air, collisions between molecules and the wall will become dominant compared to collisions between molecules, and the transfer of heat caused by convection will be suppressed. Therefore, the inventors of the present utility model have found that by specifying the volume ratio of pores 2 having a diameter of less than 68nm, which is the mean free path of air, it is possible to suppress heat transfer caused by convection and further improve the thermal insulation performance.

[0072] If the total volume of the pores 2 with a mode diameter of 68 nm or less is less than 10% of the total volume of the pores 2, heat is transferred by convection and heat conduction, so that excellent thermal insulation performance cannot be obtained. Therefore, the total volume of the pores 2 with a mode diameter of 68 nm or less is 10% or more, preferably 15% or more, relative to the total volume of the pores 2.

[0073] On the other hand, in the present embodiment, the upper limit of the total volume ratio of the pores 2 having a mode diameter of 68 nm or less is not particularly limited.

[0074] The heat transfer suppressing sheet of the present embodiment may contain various components in addition to the dry silica particles. However, the ratio of the total volume of pores of 68 nm or less does not change unless a large amount of nano-scale materials are intentionally contained.

[0075] Here, the mode diameter and volume of the pores 2 formed inside the heat transfer suppressing sheet 10 can be obtained by mercury intrusion porosimetry. In addition, the total volume ratio Vr of the pores 2 having a mode diameter of 68 nm or less can be calculated by the following formula.

[0076] Vr=(Vs / Va)×100

[0077] Here, Vs represents the total volume of the pores 2 having a mode diameter of 68 nm or less, and Va represents the total volume of all the pores Va. In addition, Vr represents the total volume ratio of the pores 2 having a mode diameter of 68 nm or less.

[0078] (Total volume of pores: 2.0cc / g or more)

[0079] The heat transfer suppression sheet of this embodiment contains dry silica particles having an average primary particle size of 25 nm or less, and has a plurality of pores formed therein. In particular, by manufacturing the heat transfer suppression sheet using a dry method, the total volume (total volume) of pores of all sizes can be increased, thereby improving the thermal insulation. Therefore, the total volume of the pores relative to the unit mass of the heat transfer suppression sheet is preferably 2.0 cc / g or more.

[0080] In addition, if Figure 4 As shown in FIG. 1 , the mode diameter of the pores formed in the heat transfer suppressing sheet 10 is proportional to the average primary particle size of the dry silica particles 1. Figure 5 As shown in the figure, as the average primary particle size of the dry silica particles 1 increases, the volume fraction of pores below 68 nm decreases. In particular, when the average primary particle size of the dry silica particles 1 exceeds 25 nm, the volume fraction of pores below 68 nm is less than 10%, and the thermal insulation performance is significantly reduced. It can be seen from this that in order to control the volume fraction of pores below 68 nm within the above range, it is necessary to use dry silica particles 1 with an average primary particle size of 25 nm or less.

[0081] Next, components contained in the heat transfer suppressing sheet of the present embodiment will be described in more detail.

[0082] <Other inorganic particles>

[0083] The heat transfer suppression sheet 10 of the present embodiment may contain only dry silica particles as inorganic particles, or may contain other inorganic particles. As the type of other inorganic particles, from the viewpoint of heat transfer suppression effect, it is preferred to use particles composed of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles, and more preferably oxide particles. In addition, there is no particular limitation on the shape, and it is preferred to include at least one selected from hollow particles and porous particles. Specifically, inorganic hollow spheres such as microporous particles, hollow silica particles, particles composed of thermally expandable inorganic materials, particles composed of water-containing porous bodies, etc. may also be used.

[0084] In addition, in addition to the above-mentioned dry silica particles 1, if one or more inorganic particles with different heat transfer suppression effects are used in combination, the heat generating body can be cooled in multiple stages, and the heat absorption effect can be exhibited in a larger temperature range. Specifically, if large-diameter particles are mixed, the small-diameter dry silica particles will enter the gaps between the large-diameter inorganic particles, thereby forming a denser structure, which can improve the heat transfer suppression effect. Below, the inorganic particles other than the dry silica particles that can be contained in the heat transfer suppression sheet 10 of this embodiment are further described in detail.

[0085] (Oxide particles)

[0086] The refractive index of oxide particles is high, and the effect of diffuse reflection of light is strong. Therefore, if oxide particles are used, radiant heat transfer can be suppressed, especially in high temperature areas such as abnormal heating. As oxide particles, it is preferred to use at least one metal oxide particle selected from titanium dioxide, zirconium oxide, zircon, barium titanate, zinc oxide and aluminum oxide. In addition, in addition to the dry silica particles 1, the above-mentioned oxide particles may contain only one kind or two or more kinds. In particular, titanium dioxide is a component with a higher refractive index than other metal oxides, diffusely reflects light in high temperature areas above 500°C, and has a high effect of shielding radiant heat. Therefore, in this embodiment, in addition to the dry silica particles 1, titanium dioxide is preferably included.

[0087] (Average primary particle size of oxide particles: 1 μm or more and 50 μm or less)

[0088] In this embodiment, the average primary particle size of the dry silica particles 1 is as described above, but in addition, the oxide particles that can be included in the heat transfer suppression sheet 10 may affect the effect of reflecting radiant heat. Therefore, if the average primary particle size of other oxide particles is limited to a predetermined range, higher thermal insulation can be obtained.

[0089] The average primary particle size of the oxide particles other than the several-form silica particles 1 is greater than 1 μm, which is sufficiently larger than the wavelength of light that contributes to heating, and the light is efficiently diffusely reflected. Therefore, in the high temperature region above 500°C, the radiation heat transfer of heat in the heat transfer suppression sheet is suppressed, and the thermal insulation can be further improved.

[0090] On the other hand, if the average primary particle size of the oxide particles other than the several-form silica particles 1 is less than 50 μm, the contact points or number between the particles will not increase even if compressed, and it will be difficult to form a path for conductive heat transfer. Therefore, the impact on the thermal insulation properties in the normal temperature region where conductive heat transfer is dominant can be particularly reduced.

[0091] Therefore, the average primary particle size of the oxide particles other than the dry silica particles 1 is preferably 1 μm or more and 50 μm or less, more preferably 5 μm or more and 30 μm or less, and most preferably 10 μm or less.

[0092] In the present embodiment, the average primary particle size of each particle contained in the heat transfer suppressing sheet 10 can be determined by observing the particles with a microscope, comparing with a standard scale, and taking the average value of arbitrary 10 particles.

[0093] (Carbide particles)

[0094] Examples of carbide particles include silicon carbide.

[0095] (Inorganic hydrate particles)

[0096] When the inorganic hydrate particles are exposed to heat from the heating element and reach a temperature above the thermal decomposition start temperature, they undergo thermal decomposition, releasing their own crystal water to lower the temperature of the heating element and its surroundings, demonstrating the so-called "endothermic effect." In addition, after releasing the crystal water, they become porous and exhibit a heat-insulating effect through countless air pores.

[0097] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), zinc hydroxide (Zn(OH)2), iron hydroxide (Fe(OH)2), manganese hydroxide (Mn(OH)2), zirconium hydroxide (Zr(OH)2) and gallium hydroxide (Ga(OH)3).

[0098] For example, aluminum hydroxide has about 35% of crystal water, and as shown in the following formula, it undergoes thermal decomposition to release crystal water, exhibiting an endothermic effect. Moreover, after releasing the crystal water, it becomes a porous aluminum oxide (Al2O3), which has the function of a heat insulator.

[0099] 2Al(OH)3→Al2O3+3H2O

[0100] In addition, as described later, the heat transfer suppression sheet 10 of the present embodiment is preferably interposed between battery cells, for example, but in a battery cell that has thermal runaway, the temperature rises sharply to more than 200° C., and the temperature continues to rise to around 700° C. Therefore, it is also preferred to contain inorganic particles composed of an inorganic hydrate having a thermal decomposition starting temperature of 200° C. or more.

[0101] Regarding the thermal decomposition starting temperatures of the inorganic hydrates listed above, aluminum hydroxide is about 200°C, magnesium hydroxide is about 330°C, calcium hydroxide is about 580°C, zinc hydroxide is about 200°C, iron hydroxide is about 350°C, manganese hydroxide is about 300°C, zirconium hydroxide is about 300°C, and gallium hydroxide is about 300°C. They all roughly overlap with the temperature range of the rapid temperature rise of the battery cell that undergoes thermal runaway, and can effectively suppress the temperature rise. Therefore, they can be said to be preferred inorganic hydrates.

[0102] (Average secondary particle size of inorganic hydrate particles: 0.01 μm or more and 200 μm or less)

[0103] When the heat transfer suppression sheet contains inorganic hydrate particles, if the average particle size is too large, it takes a certain amount of time for the inorganic hydrate particles near the center of the heat transfer suppression sheet 10 to reach their thermal decomposition temperature, so the inorganic hydrate particles near the center of the sheet may not be completely thermally decomposed. Therefore, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.

[0104] (Particles composed of heat-expandable inorganic material)

[0105] The heat transfer suppressing sheet 10 preferably further contains particles made of a heat-expandable inorganic material. Examples of the heat-expandable inorganic material include vermiculite, bentonite, mica, and perlite.

[0106] (Particles composed of a porous body containing water)

[0107] The heat transfer suppressing sheet 10 preferably contains particles composed of a hydrous porous body. Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, aerogel, mica, vermiculite and the like.

[0108] (Inorganic hollow sphere)

[0109] The heat transfer suppression sheet 10 preferably further includes inorganic hollow spheres. The inorganic hollow spheres have an effect of suppressing convective heat transfer or conductive heat transfer of heat in the heat transfer suppression sheet 10 in a temperature range below 500° C., and thus can further improve the heat insulation performance of the heat transfer suppression sheet 10. As the inorganic hollow spheres, at least one selected from white sand hollow spheres, silica hollow spheres, fly ash hollow spheres, barite hollow spheres, and glass hollow spheres can be used.

[0110] The content of the inorganic particles in the heat transfer suppressing sheet 10 can be calculated, for example, by heating the heat transfer suppressing sheet at 800° C. to decompose the organic components and then measuring the mass of the remaining components.

[0111] In addition, the heat transfer suppressing sheet 10 of the present embodiment may contain organic fibers and inorganic fibers in addition to the dry silica particles 1 and other inorganic particles. Furthermore, all of these fibers and particles may be held by the binder part 3 containing an organic material.

[0112] <Organic Fiber>

[0113] When the heat transfer suppressing sheet 10 includes organic fibers, the strength and shape of the sheet can be maintained. The organic material constituting the organic fibers is not particularly limited, and examples thereof include organic fibers composed of at least one selected from polyethylene terephthalate, polyethylene, polypropylene, and nylon.

[0114] (Fiber length of organic fibers)

[0115] The fiber length of the organic fibers is not particularly limited, but from the viewpoint of ensuring moldability and processability, the average fiber length of the organic fibers is preferably 10 mm or less.

[0116] On the other hand, from the viewpoint of allowing the organic fibers to function as a skeleton and ensuring the compressive strength of the heat transfer suppressing sheet, the average fiber length of the organic fibers is preferably 0.5 mm or more.

[0117] (Organic fiber content)

[0118] In the present embodiment, if the content of the organic fiber in the heat transfer suppressing sheet 10 is appropriately controlled, a sufficient reinforcement effect of the skeleton can be obtained.

[0119] The content of the organic fiber is preferably 5% by mass or more, and more preferably 10% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the content of the organic fiber is too high, the content of the dry silica particles 1 will be relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the organic fiber is preferably 25% by mass or less, and more preferably 20% by mass or less, relative to the total mass of the heat transfer suppression sheet.

[0120] (Core-sheath structure binder fiber)

[0121] As the organic fiber, an adhesive fiber of a core-sheath structure may be included, wherein the adhesive fiber of the core-sheath structure has a core extending along the length direction of the fiber and a sheath formed in a manner of covering the outer peripheral surface of the core. In the adhesive fiber of the core-sheath structure, the melting point of the organic material constituting the sheath is preferably lower than the melting point of the organic material constituting the core. Depending on the temperature of manufacturing the heat transfer suppression sheet 10 and the melting points of the organic materials constituting the core and the sheath, when manufacturing the heat transfer suppression sheet, only the core remains in the shape of organic fibers, and the sheath becomes an adhesive part in a state of containing inorganic particles, a part of which is melted to the core. In this way, if an adhesive fiber of a core-sheath structure is used, both the effect of maintaining the strength and shape of the heat transfer suppression sheet 10 and the effect of improving the retention of inorganic particles or other materials containing dry silica particles 1 can be achieved.

[0122] In addition, even when using organic fibers without a core-sheath structure, the core of the organic fibers can be left and only the surface can be melted, and the inorganic particles can be coated on the surface, depending on the temperature setting. In this way, both the effect of maintaining the strength and shape of the heat transfer suppression sheet 10 and the effect of improving the retention of the inorganic particles can be achieved. However, since temperature adjustment during manufacturing becomes difficult, when using organic fibers as the material constituting the heat transfer suppression sheet 10, it is more preferable to use a binder fiber with a core-sheath structure.

[0123] As the organic material constituting the core, at least one selected from polyethylene terephthalate, polypropylene and nylon can be selected. In addition, as the organic material constituting the sheath, at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon can be selected. The melting point of the organic material constituting the sheath is preferably above 90°C, more preferably above 100°C, preferably below 150°C, more preferably below 130°C. In addition, the melting point of the organic material constituting the core is preferably higher than the melting point of the organic material constituting the sheath by more than 60°C, more preferably higher than 70°C, and further preferably higher than 80°C.

[0124] Binder fibers having a core-sheath structure as described above are usually sold on the market, and the materials constituting the core and the sheath may be the same or different from each other. Examples of binder fibers whose core and the sheath are made of the same material and have different melting points include binder fibers whose core and the sheath are made of polyethylene terephthalate, binder fibers made of polypropylene, and binder fibers made of nylon. Examples of binder fibers whose core and the sheath are made of different materials include binder fibers whose core is made of polyethylene terephthalate and whose sheath is made of polyethylene; and binder fibers whose core is made of polypropylene and whose sheath is made of polyethylene.

[0125] In this embodiment, the melting point of the organic material constituting the sheath of the binder fiber refers to the melting temperature at which the organic material begins to melt and deform, but softening accompanied by shape change is also considered as a type of melting deformation. The melting point of the sheath of the binder fiber can be measured, for example, by the following method.

[0126] The binder fiber to be measured is arranged in contact with the glass fiber having a higher melting point, and is heated from room temperature to, for example, 200°C at a heating rate of 5°C / min, and then cooled to room temperature. At this time, if the surface of the binder fiber undergoes melting deformation and welding occurs at the portion in contact with the glass fiber, or if the cross-sectional shape of the binder fiber changes, it can be determined that the melting point of the organic material constituting the sheath is 200°C or less. In this embodiment, the heating temperature is varied, and the melting state of the binder fiber and the glass fiber after cooling or the cross-sectional shape of the binder fiber is observed by the above method, thereby determining the melting point of the organic material constituting the sheath.

[0127] (Other organic materials)

[0128] The heat transfer suppression sheet 10 of this embodiment may also contain hot-melt powder as other organic materials. Hot-melt powder is a powder having the property of melting by heating. When using hot-melt powder as the material of the heat transfer suppression sheet 10, when manufacturing the heat transfer suppression sheet 10, the hot-melt powder is melted by heating the material mixture. Then, when the material mixture is cooled, the hot-melt powder in a molten state solidifies in a state containing the surrounding materials such as the dry silica particles 1, forming an adhesive portion 3. Thereby, the holding power of the material can be further improved. In addition, as the components constituting the hot-melt powder, polyethylene, polyester, polyamide, ethylene vinyl acetate, etc. can be listed.

[0129] [Method for producing heat transfer suppressing sheet]

[0130] The method for producing the heat transfer suppressing sheet 10 of the present embodiment includes a step of processing a material mixture including dry silica particles 1 into a sheet shape by a dry method. The method for producing the heat transfer suppressing sheet will be described in further detail.

[0131] (Processing steps)

[0132] First, the dry silica particles 1 and any material, such as a binder material, are put into a mixer such as a V-type mixer in a specified ratio to prepare a material mixture. In the present embodiment, since the heat transfer suppression sheet 10 is manufactured by a dry method, a solvent such as water required for molding by a wet method is not added to the material mixture. However, in order to prevent the dry silica particles 1 and other powders from flying and the handling of the raw materials from becoming difficult during the manufacture of the heat transfer suppression sheet 10, a small amount of solvent such as water can be added within the scope of the dry method in the present embodiment. For example, by adding a small amount of solvent such as water to the material mixture, the scattering of the dry silica particles 1 during manufacturing can be further suppressed.

[0133] Then, the obtained material mixture is put into a predetermined mold, pressurized by a press machine or the like, and the obtained molded body (not shown) is heated. At this time, the binder material is melted by heating. Then, when the heated material mixture is cooled, the binder material in a molten state solidifies in a state including the surrounding materials such as the dry silica particles 1, thereby forming the binder portion 3. Thus, a heat transfer suppression sheet 10 processed into a sheet shape can be obtained.

[0134] In the present invention, there is no particular limitation on the manufacturing conditions such as pressurization conditions. The heat transfer suppressing sheet 10 can be obtained by appropriately adjusting the mass of the material mixture and the volume of the molding die for processing the heat transfer suppressing sheet 10 into a sheet shape.

[0135] The dry silica particles 1 used in the manufacturing method of this embodiment are the dry silica particles 1 described in the above-mentioned [heat transfer suppressing sheet] column, and the average primary particle size is 25 nm or less. Thus, by using the dry silica particles 1 with strictly controlled average primary particle size, the total volume of the pores 2 with a mode diameter of 68 nm or less can be made 10% or more relative to the total volume of the pores. As a result, as described above, the heat insulation can be further improved compared with the conventional heat transfer suppressing sheet.

[0136] In addition, when using a core-sheath structured binder fiber as the binder material, the core can be left and the sheath can be melted by appropriately adjusting the heating temperature. Specifically, the heating temperature is preferably set to a temperature higher than the melting point of the organic material constituting the sheath and lower than the melting point of the organic material constituting the core.

[0137] The heating temperature in the heating step is preferably set to be 10°C or higher than the melting point of the organic material constituting the sheath, and more preferably 20°C or higher. On the other hand, the heating temperature is preferably set to be 10°C or lower than the melting point of the organic fiber constituting the core, and more preferably 20°C or lower. In addition, the heating time is not particularly limited, but it is preferably set to a heating time for allowing the sheath to fully melt. For example, it can be set to be 3 minutes or more and within 15 minutes.

[0138] In the heat transfer suppression sheet of the present embodiment, when the core-sheath structured adhesive fibers are used as the adhesive material, when the material mixture is cooled while the core remains and the sheath is melted, the strength of the heat transfer suppression sheet can be ensured by the core. In addition, after cooling, an adhesive portion 3 containing dry silica particles and the like is formed, so that the dry silica particles and the like can be retained. In addition, the adhesive portion is welded around the core portion in a state containing dry silica particles, and since the core portion has a thicker fiber diameter, a high-strength heat transfer suppression sheet can be obtained. Furthermore, in the material mixture, the core-sheath structured adhesive fibers exist in irregular directions, and when a portion of the adhesive fibers are in contact with each other, the adjacent core portions are welded to each other through the adhesive portion formed by the melting of the sheath portion to form a three-dimensional skeleton. As a result, the overall shape of the heat transfer suppression sheet can be further maintained with high strength.

[0139] Alternatively, an adhesive such as hot melt powder may be used as the material of the heat transfer suppressing sheet 10. When the type and content of the hot melt powder are appropriately adjusted, the holding power of the dry silica particles 1 and the like can be increased, and powder loss can be further suppressed.

[0140] In order to further suppress the powdering, the surface of the heat transfer suppressing sheet 10 may be covered with a film or the like. Examples of the polymer film include films made of polyimide, polycarbonate, PET, paraphenylene sulfide, polyetherimide, cross-linked polyethylene, flame-retardant chloroprene rubber, polyvinylidene fluoride, rigid vinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PCV, flame-retardant PET, polystyrene, polyethersulfone, polyamide-imide, polyacrylonitrile, polyethylene, polypropylene, polyamide, etc. The method of covering the surface of the heat transfer suppressing sheet 10 with a film is not particularly limited, and examples thereof include a method of attaching the heat transfer suppressing sheet 10 with an adhesive or the like, a method of wrapping the heat transfer suppressing sheet 10 with a film, a method of shrink-wrapping the heat transfer suppressing sheet 10 with a film, and a method of housing the heat transfer suppressing sheet 10 in a bag-like film.

[0141] In the method for manufacturing a thermally conductive suppressing sheet of the present embodiment, the content of the dry silica particles 1 and other inorganic particles and organic fibers that may be contained as materials relative to the total mass of the solid components in the material mixture is the same as the preferred content of each component in the thermally conductive suppressing sheet 10. That is, the content of the dry silica particles 1 relative to the total mass of the solid components in the material mixture is preferably 50% by mass or more. In addition, the content of the dry silica particles 1 relative to the total mass of the solid components in the material mixture is preferably 80% by mass or less.

[0142] In addition, in order to obtain the reinforcement effect of the skeleton and the retention effect of the material, when the organic fiber (binder fiber of the core-sheath structure) is mixed in the material mixture, the content of the organic fiber relative to the total mass of the solid components in the material mixture is preferably 5% by mass or more, and more preferably 10% by mass or more. On the other hand, in order to obtain the desired thermal insulation performance, the content of the organic fiber relative to the total mass of the solid components in the material mixture is preferably 25% by mass or less, and more preferably 20% by mass or less.

[0143] In order to obtain the effect of suppressing powder shedding, when hot-melt powder is mixed in the material mixture, the content of hot-melt powder relative to the total mass of solid components in the material mixture is preferably 0.5 mass% or more, and more preferably 1 mass% or more. In addition, in order to obtain the desired thermal insulation performance, when hot-melt powder is mixed in the material mixture, the content of hot-melt powder relative to the total mass of solid components in the material mixture is preferably 5 mass% or less, and more preferably 4 mass% or less.

[0144] <Thickness of Heat Transfer Suppression Sheet>

[0145] The thickness of the heat transfer suppression sheet 10 of this embodiment is not particularly limited, but is preferably 0.05 mm or more and 10 mm or less. When the thickness is 0.05 mm or more, sufficient compressive strength can be obtained. On the other hand, when the thickness is 10 mm or less, good thermal insulation of the heat transfer suppression sheet 10 can be obtained.

[0146] [Battery Pack]

[0147] Figure 6 The battery pack 100 of the present embodiment includes a plurality of battery cells 20a, 20b, 20c connected in series or in parallel and the heat transfer suppression sheet 10 of the present embodiment.

[0148] For example, Figure 6As shown, the heat transfer suppression sheet 10 of this embodiment is interposed between the battery cell 20a and the battery cell 20b, and between the battery cell 20b and the battery cell 20c. The battery cells 20a, 20b, 20c and the heat transfer suppression sheet 10 are housed in the battery case 30.

[0149] In addition, the heat transfer suppressing sheet 10 is as described above.

[0150] In the battery pack 100 configured in this way, even if a battery cell 20a reaches a high temperature, the heat transfer suppressing sheet 10 having an excellent heat transfer suppressing effect is present between the battery cell 20b, thereby suppressing the heat transfer to the battery cell 20b.

[0151] In addition, the heat transfer suppression sheet 10 of the present embodiment contains the dry silica particles 1 and has high compressive strength, so that even when the battery cells 20a, 20b, and 20c are charged and discharged, the thermal expansion of these battery cells can be suppressed. Therefore, the distance between the battery cells can be ensured, the excellent heat insulation performance can be maintained, and the thermal runaway of the battery cells can be prevented.

[0152] In addition, the battery pack 100 of this embodiment is not limited to Figure 6 Specifically, the heat transfer suppression sheet 10 may be disposed not only between the battery cell 20a and the battery cell 20b and between the battery cell 20b and the battery cell 20c, but also between the battery cells 20a, 20b, 20c and the battery case 30.

[0153] In the battery pack 100 configured in this manner, when a battery cell catches fire, it is possible to suppress the flame from spreading to the outside of the battery case 30 .

[0154] For example, the battery pack 100 of the present embodiment is used in an electric vehicle (EV) or the like, and may be arranged under the floor of passengers. In this case, even if a battery cell catches fire, the safety of passengers can be ensured.

[0155] In addition, the heat transfer suppression sheet 10 is not only between the battery cells, but can also be arranged between the battery cells 20a, 20b, 20c and the battery case 30, so there is no need to re-produce fireproof parts, etc., and a low-cost and safe battery pack 100 can be easily constructed.

[0156] In the battery pack of this embodiment, the heat transfer suppression sheet 10 disposed between the battery cells 20a, 20b, 20c and the battery case 30 may be in contact with the battery cells or may have a gap therebetween. However, if there is a gap between the heat transfer suppression sheet 10 and the battery cells 20a, 20b, 20c, even if the temperature of any of the plurality of battery cells rises and the volume expands, deformation of the battery cell can be allowed.

[0157] In addition, the heat transfer suppression sheet 10 of this embodiment can be made into various shapes by its manufacturing method. Therefore, it is not affected by the shape of the battery cells 20a, 20b, 20c and the battery case 30, and can be applied to any shape. Specifically, in addition to square batteries, it can also be applied to cylindrical batteries, flat batteries, etc.

[0158] Above, various embodiments have been described, but the present invention is certainly not limited to such examples. It is clear to those skilled in the art that various variations or modifications can be thought of within the scope of the application documents, and it should be understood that they will naturally fall within the technical scope of the present invention. In addition, within the scope of not departing from the gist of the utility model, the various constituent elements in the above-mentioned embodiments may also be combined arbitrarily.

[0159] In addition, this application is an application based on the Japanese patent application (Japanese Patent Application No. 2023-053781) filed on March 29, 2023, and the contents thereof are incorporated herein by reference.

Claims

1. A heat transfer suppressing sheet comprising dry silica particles and having pores therein, characterized in that: The average primary particle size of the dry silica particles is less than 25 nm. The total volume of the pores having a mode diameter of 68 nm or less is 10% or more of the total volume of the pores.

2. The heat transfer suppressing sheet according to claim 1, wherein: The dry silica particles have an average primary particle size of 7 nm or more.

3. The heat transfer suppression sheet according to claim 1, wherein: The total volume of the pores having a mode diameter of 68 nm or less is 15% or more of the total volume of the pores.

4. The heat transfer suppressing sheet according to claim 1, wherein: The total volume of the pores is 2.0 cc / g or more.

5. The heat transfer suppression sheet according to claim 1, wherein: In the heat transfer suppressing sheet, the small-diameter dry silica particles enter into gaps between the large-diameter inorganic particles.

6. The heat transfer suppressing sheet according to claim 5, wherein: The inorganic particles and the dry silica particles are held by a binder portion.

7. The heat transfer suppressing sheet according to any one of claims 1 to 6, characterized in that: The surface of the heat transfer suppressing sheet is covered with a film.

8. A battery pack, characterized in that: The battery pack comprises a plurality of battery cells and the heat transfer suppression sheet according to any one of claims 1 to 7, The plurality of battery cells are connected in series or in parallel.

9. The battery pack according to claim 8, characterized in that: The heat transfer suppression sheet is disposed between battery cells and / or between a battery cell and a battery case.